2017
DOI: 10.1111/jace.15335
|View full text |Cite
|
Sign up to set email alerts
|

Coupling copper and hydrogenated TiO2 to bare TiO2 structures for improved photocatalytic performance

Abstract: Coupling of metals and hydrogenated TiO 2 (HT) to bare TiO 2 may improve synergistically the photocatalytic activity of TiO 2 for pollutant decomposition.Herein, we address this issue by investigating the photocatalytic performances of Cu-loaded HT (CuHT)/bare TiO 2 (CuHTT) heterojunction nanocomposites for the degradation of harmful n-butanol under simulated solar light illumination. CuHTT with a CuHT-to-TiO 2 composition ratio of 0.1 showed a photocatalytic efficiency exceeding those of four reference photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(42 reference statements)
2
5
0
Order By: Relevance
“…The electrons (e − ) excited by light can reduce O 2 to . O 2 − , [33–35] but the VB potential (3.32) of ECF is larger than standard H 2 O/ . OH (2.4 eV vs. NHE).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The electrons (e − ) excited by light can reduce O 2 to . O 2 − , [33–35] but the VB potential (3.32) of ECF is larger than standard H 2 O/ . OH (2.4 eV vs. NHE).…”
Section: Resultsmentioning
confidence: 88%
“…In addition, the CB potential of Cu 7 S 4 (À 1.06 eV, vs. NHE) is smaller than that of O 2 / * O 2 À (À 0.33 eV, vs. NHE). [32] The electrons (e À ) excited by light can reduce O 2 to O 2 À , [33][34][35] but the VB potential (3.32)…”
Section: Analysis Of Photocatalytic Mechanismmentioning
confidence: 99%
“…The model gas-phase pollutants were periodically measured at the inlet and outlet portions of the reaction vessel using an adsorbent tube [29]. The model pollutants (nBT and oXYL) adsorbed on the sampling tube were determined using a pretreatment unit/Perkin Elmer gas chromatography/mass spectrometry (GC/MS) system.…”
Section: Measurement Of the Model Gas-phase Pollutantsmentioning
confidence: 99%
“…Because such a hybrid structure can efficiently separate photo‐generated holes and electrons, and as a consequence greatly enhance the photocatalytic efficiency. For instance, Han et al reported that the hybrid nanostructure of CdS‐Au exhibited enhanced photocatalytic efficiency compared with pure CdS spherical nanoparticles toward the photodegradation of rhodamine B. Cu/hydrogenated TiO 2 /TiO 2 was prepared toward photocatalytic degradation of n‐butanol . Other similar hybrid structures such as AgBr‐Ag and TiO 2 ‐PtPd with improved photocatalysis performance were also successfully fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Han et al 18 reported that the hybrid nanostructure of CdS-Au exhibited enhanced photocatalytic efficiency compared with pure CdS spherical nanoparticles toward the photodegradation of rhodamine B. Cu/hydrogenated TiO 2 /TiO 2 was prepared toward photocatalytic degradation of n-butanol. 19 Other similar hybrid structures such as AgBr-Ag 5 and TiO 2 -PtPd 20 with improved photocatalysis performance were also successfully fabricated. However, fabrication of the aforementioned hybrid photocatalysts mainly uses the noble metals, which are very expensive.…”
Section: Introductionmentioning
confidence: 99%